Self-defense in Islamic and International Law - Shah, N. author. aut Link
XIII, 192 p.
Keywords: The book argues that the concept of self-defense in Islamic and International law is compatible. Al-Qaeda's declaration of Jihad does not meet the Islamic legal test. Similarly, the invasion of Iraq does meet the international legal test.